Self-reported speed compliance and attitudes towards speeding in a representative sample of drivers in Australia. (June 2017) - Stephens, A.N.; Nieuwesteeg, M.; Page-Smith, J.; Fitzharris, M.
Highlights: Speed behaviour and attitudes measured in a large sample of drivers in Australia (5179). Almost half (47%) of the sample reported normally driving above the speed limit. Age and sex were related to speed non-compliance, with males being more excessive speeders. When compared to compliant drivers, non-compliant drivers perceived less risk of serious crash and/or enforcement. Abstract: Background: Vehicle speed is a major contributor to road trauma, both in terms of increased crash risk and injury severity. In Australia, approximately one third of fatal crashes occur in speed zones of 100 km/h. This proportion has remained the same, despite the reduction in the number of road fatalities over the past decade. To drive further reductions in speed-related crashes, an improved understanding of the underlying determinants of speed choice is required. Method: A community attitude survey designed to understand speed behaviour and attitudes towards speeding was distributed to a large (N = 5179) representative sample of drivers in Australia. Participants provided information regarding their normal speed choices across four different speed zones (40, 50, 60 and 100 km/h), beliefs about the risks and enforcement of speeding behaviour as well as technology to reduce speeding. Results: Almost half of the sample (47%) reported exceeding the speed limit in 100 km/h zones, although only a small number of these drivers (<0.5%) did so by 11 km/h or more. Age and sex were related to speed limit non-compliance. Males were more likely to be classified as mid-level speeders, defined as being up to 10 km/h over the limit, and excessive speeders (11 + km/h over the limit). Younger drivers were also more likely to be non-compliant. When compared to compliant drivers, non-compliers perceived less risk of a serious crash, reported greater likelihood of exceeding the speed limit when they believed they would not be detected, and reported a higher level of social acceptability of speeding. Only one-third of the sample reported prior knowledge of intelligent speed assist (ISA) technology, however, once explained, the majority agreed it would be personally useful (64%). Speed non-compliers were somewhat less likely to support the usefulness of ISA than speed limit compliant drivers. Conclusion: These findings can be used to target appropriate interventions and road safety messages, aimed at reducing speeding behaviour. Measures designed to address perceived social acceptability of speed behaviour, the increased crash risk associated with speeding, and the threat of detection are recommended.